2022
DOI: 10.2147/dddt.s362754
|View full text |Cite
|
Sign up to set email alerts
|

Isoliquiritigenin Ameliorates Ischemia-Induced Myocardial Injury via Modulating the Nrf2/HO-1 Pathway in Mice

Abstract: Background Oxidative stress and inflammatory reaction play critical roles in acute myocardial infarction (AMI). Isoliquiritigenin (ISL), a flavonoid monomer extracted from licorice, has been found to have antioxidant and anti-inflammatory effects in cancer studies. Here, we tested the effect and underlying mechanisms of ISL on ischemia-induced myocardial injury in a mouse AMI model. Methods Adult C57BL/6 mice were pre-treated by intraperitoneal injection of ISL and/or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 50 publications
(55 reference statements)
1
7
0
Order By: Relevance
“…In addition, the pathogenesis of AMI is associated with the excessive production of reactive oxygen species (ROS), which induce oxidative stress. Oxidative stress is the main cause of the poor prognosis of ischemic myocardial injury in AMI [ 17 ]. Several other studies have also identified oxidative stress as a key factor in AMI [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the pathogenesis of AMI is associated with the excessive production of reactive oxygen species (ROS), which induce oxidative stress. Oxidative stress is the main cause of the poor prognosis of ischemic myocardial injury in AMI [ 17 ]. Several other studies have also identified oxidative stress as a key factor in AMI [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, this kind of pharmacological strategy requires su cient drug concentrations in the lesion, thus the drugs need to be administered before infarction. The MI mice were pre-treated by intraperitoneal injection of isoliquiritigenin for 3 days prior to the surgery to ameliorate MI injury [41]. Huoxin pill was administered via oral gavage prior to MI operation to prevent acute MI injury [42].…”
Section: Discussionmentioning
confidence: 99%
“…In an LAD-induced MI model, isoliquiritigenin (ISL) or icariin significantly reduced the myocardial infarction area, improved cardiac function, inhibited ROS and MDA production, suppressed SOD and GPx consumption through increased nuclear Nrf2 and cytosolic HO-1 levels and reduced OS after AMI (Sai et al, 2022;D. Yao et al, 2022).…”
Section: Flavonoidsmentioning
confidence: 99%
“…In an LAD-induced MI model, isoliquiritigenin (ISL) or icariin significantly reduced the myocardial infarction area, improved cardiac function, inhibited ROS and MDA production, suppressed SOD and GPx consumption through increased nuclear Nrf2 and cytosolic HO-1 levels and reduced OS after AMI ( Sai et al, 2022 ; D. Yao et al, 2022 ). Furthermore, in mice or rats with STZ-induced diabetes mellitus or high glucose-cultured H9c2, ISL attenuated inflammation and OS and protected against aortic injury through upregulation of Nrf2 and HO-1 (X.…”
Section: Protective Effects Of Natural Products On Cvdsmentioning
confidence: 99%